Hida Scan in The Follow-Up of Biliary-Enteric Anastomoses. Issue 1 (1988) - Belli, G.; Romano, G.; Monaco, A.; Santangelo, M. L.
Abstract : In order to assess the patency and function of biliary-enteric anastomoses performed in our Department of Surgery, 21 patients entered the following study, provided an informed consent was obtained. All the patients were affected by benign biliary tract diseases and underwent either Roux-en-Y hepaticojejunostomy (11 cases), or side-to-side choledochoduodenostomy (10 cases). The 21 patients were evaluated with Tc-99m-HIDA scanning at intervals of 20 days–36 months after the surgical procedure (mean 14 months). The images were obtained after intravenous injection of the radioactive medium (5 mCi) and the scans were taken at 1 min (1 frame/s), 3 min (1 frame/10 s), and 56 min (1 frame/2 min). The data were analyzed by a Digital PDP 11/34 Computer System. This method allowed us to assess each individual patient for the patency of the anastomosis and, by computer analysis, to build up a profile of the timing of the passage of the radioactive medium through the anastomosis; a delayed passage across the anastomosis was always pathological. In conclusion, the 99m-Tc-HIDA scanning used in our study for long-term follow-up of biliary-enteric anastomoses is reliable and allows an assessment of prognosis.